PNEUMONIA IN ICU HOSPITALIZED NEUROLOGIC PATIENTS: THE RELATIONSHIP BETWEEN C-REACTIVE PROTEIN AND PROCALCITONIN LEVELS WITH THE RESULTS OF BLOOD AND SPUTUM CULTURES - Indah, Carolin Tiara Lestari; Widyantara, I Wayan; Putra, Ida Bagus Kusuma; Tini, Kumara (MNJ (Malang Neurology Journal), 2024)
Background: Pneumonia is often experienced by neurology patients, especially in the intensive care unit (ICU). Culture and antibiotic sensitivity tests as the gold standard of pneumonia require a long time, then other examinations are needed, namely C-reactive protein markers (CRP), and procalcitonin (PCT). Objective: To determine the relationship between CRP and PCT levels with the results of blood and sputum cultures in ICU hospitalized neurologic patients Prof I.G.N.G. Ngoerah General Hospital, Denpasar, Bali. Methods: A cross-sectional study that includes all neurology patients with pneumonia in the ICU of Prof I.G.N.G. Ngoerah General Hospital in 2018-2022. The required examination data are demographic data, CRP and procalcitonin levels, and blood and sputum culture results. Data analysis using SPSS Version 24 qualitatively. Results: We identified 121 ICU hospitalized neurologic patients with pneumonia involving 59 blood and 85 sputum culture-positive and 15 isolated pathogens. The leading pathogens were Klebsiella pneumoniae, Acinetobacter baumanii, Pseudomonas aeuroginosa, Escherichia coli, Staphylococcus aureus,  Candida albican, Streptococcus suis, and Staphylococcus haemolyticus, and other pathogens which were isolated in 31 (19,7%), 25 (15.9%), 20 (12.7%), 11 (7%), 10 (6.4%), 4 (2.5%), 3 (1.9%), and 1 (0.6%) cases, respectively, however Klebsiella pneumoniae has the highest number of resistance cases, especially ESBL. There was a significant relationship between high CRP (>97.9) and blood culture (OR 6.42, p <0.03). Conclusion: CRP can be considered as a fast and appropriate examination to establish an early diagnosis of pneumonia in patients.